SOLID FUEL FROM EMPTY FRUIT BUNCH FIBER AND WASTE PAPERS PART 7: WATER ABSORPTION TEST - YAAKOB, MOHD YUHAZRI; HASOLOAN, HAERY IAN PIETER; YAHAYA, SAIFUDIN HAFIZ; SAID, MD RADZAI (Global Engineers and Technologists Review, 2012)
This research discussed on the results obtained for each sample that have been conducted to the solid fuel briquettes made of empty fruit bunch fiber and waste papers from view of physical performance which is water absorption test. This solid fuel prepared by manual compression technique. This analysis important to know the capability of the solid fuel to sustained/maintained the physical shape after immersed in water. Experimental work showed most samples behave same physical behaviors.